The Macroeconomic Effects of Monetary Policy and Government Expenses in Response to Covid-19: Evidence from Saudi Arabia - Bogari, Adel (Journal of Ecohumanism, 2024)
The purpose of this paper is to test the effectiveness of the interaction between monetary and budgetary policies during the Covid-19 crisis in Saudi Arabia. To this end, we use the Markov regimes technique to take into account change in regimes of the two policies. We adopt the SVAR modelling of sign restrictions to test the joint effect of a stagnation in tax revenues and a 1% increase in government spending over a time horizon of four periods identified as tax shocks during the Covid-19 period. The results of impulse response tests show that this shock did not lead to an improvement in industrial production. The results show tax dominance by financing state resources to compensate for the burden of government expenditure. If the central bank has raised the interest rate to anchor inflationary expectations, it will in turn have negative effects on economic activity as measured by the industrial production index. This scenario coincides with the second regime of the monetary rule, where the central bank acts in response to expected inflation.